A study on store image of FOKUS Store Pantai Dalam / Maliana Basri - Basri, Maliana (1998)
The overview of the FOKUS Store and background of company were presented in Chapter 1. This chapter also included background of the study, background of the FOKUS Store, problem statement in conducting this research, objectives of study, scope of study and the limitations of the study. Among the objectives of the study, various problems in FOKUS image were identified